Service Based Practical Technology Drinking Water Heater with Heat Smoke Recovery of Multipurpose Diesel Motorcycle Exhaust for Wooden Fisherman Boat Power - Bambang Hermani (Barakuda'45, 2022)
The gas power cycle of a four-stroke combustion engine is obtained from a mixture of diesel injection+compressed hot air as the working fluid, which in this case is taken from a versatile type of diesel engine from all kinds of fishing communities on the north coast of Java Island, it can be said that in general the use of multipurpose diesel engines used as a propulsion engine for fishing boats. A common sight for Pantura fishermen is hot smoke exhaust from the exhaust of a multipurpose diesel motor driving a wooden fishing boat released into the air. Eventually, it becomes a source of air pollution around the ship, especially nitrogen oxides, which are toxic to human respiration; hot smoke waste resulting from the combustion process released through the piston engine exhaust system still contains valuable energy potential in the form of hot gas released by the exhaust which if attempted to heat the hot gas energy before being discharged into the ambient air, the heat energy can be recovered by installing additional heat exchangers as a benefit of heat sources for heat exchange heaters or heaters the result is cold drinking water turns into hot drinking water. Heat balance is the calculation of the heat released in the combustion of fuel+air in the combustion chamber and its utilization in the transfer of cold fluids to hot fluids, which is the heat energy content of explosion in compression combustion engines based on fossil fuels. All heat products of combustion cannot be converted 100% into practical motor work or power; energy transfer is lost from the combustion motor, such as 25%, to cooling water 32%, in the exhaust gas 34%, pumping losses, 3%, losses -friction loss between parts due to lousy machining inaccuracy 6% and radiation to the air environment. A drinking water heater with hot smoke recovery from a versatile diesel motor exhaust driving a wooden fishing boat works by recovering or recovering heat energy from the exhaust gas in the exhaust directly from the combustion process cycle in a piston-type combustion engine. The hot flue gas flow is forced into direct contact with the wall of the heat exchanger tube before exiting the exhaust. As long as the piston combustion motor is running, the hot stream from the exhaust gas flows into the shell & tube heat exchanger shell. This experiment aims to get clean hot water 70OC with a linked cold water mass = 0.0064 kg/s at 28OC. Another effect of this experiment is to control exhaust emissions into the atmosphere from internal combustion engines.